(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this article, a nutritional powder from the pomace of various grape varieties was obtained in laboratory conditions and its chemical composition was analyzed. The food powder obtained from the pomace of grapes was added to wheat flour bread and its effect on quality indicators was studied.